PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN DAN PERSEPSI SISWA TERHADAP HASIL BELAJAR DI SMP - Zulyadaini Zulyadaini; Buyung Buyung (Universitas Batanghari Jambi, 2015)
The aims of this research is to know influence the instructional approach and perseption to learning outcomes. Research method is quasi-experimental disign with treatmen by level 2 X 2. Data was collected with learning outcomes test. The result of this research shows that: in total learning outcomes of students who use Contextual Teaching Learning (CTL) approach were higher than those who use conventional approach. in total learning outcomes of students on the higher perception were higher than those lower persepstion. The students with higher perseption achieved higher learning outcomes by using Contextual Teaching Learning (CTL) approach as same as used conventional approach. The students with lower perseption achieved learning outcomes by using Contextual Teaching Learning (CTL) approach as same as used conventional approach. There were several not interaction effects between the instructional approach with perseption toward the students’ learning outcomes.Keywords :Instructional Approach, Contextual Teaching And Learning (CTL) Approach, Perseption, Learning Outcomes